Gadung Chips Business Development Strategy (Dioscorea hispida L.) With SWOT Analysis - Surya Andre Ferdian Causa; Umi Kulsum Nur Qomariah; Siti Nur Qomariyah (AGARICUS: Advances Agriculture Science & Farming, 2022)
This study aims to analyze Business Development Strategy in the Home Industry of Gadung Chips (Dioscorea Hispida L.) Dua Putra Jaya in Jombang Regencyusing SWOT, EFAS, IFAS and Grand Strategy Matrix analysis methods. Sampling is done purposively or selected. This study uses primary and secondary data. Primary data obtained by observation and interviews with owners, employees Home Industry Gadung Chips (Dioscorea Hispida L.) Dua Putra Jaya and the Made Village apparatus, while secondary data were obtained from existing sources. The analysis used in determining the business development strategy of the Gadung Chips Home Industry includes evaluation of internal factors (IFAS), evaluation of external factors (EFAS), SWOT matrix and Grand Strategy matrix. The results of this study based on a SWOT analysis of internal and external factors indicate that the home industry for making Gadung chips is in quadrant type 1, which is a very profitable position oriented to aggressive growth (Growth Oriented Strategy). Keywords: Home Industry, SWOT Analysis, IFAS, EFAS, Grand Strategy Matrix.